The Prevention of Anxiety and Depression in Early Childhood - Baughman, Natalie; Prescott, Susan L.; Rooney, Rosanna (Frontiers in Psychology, 2020)
Recent statistics suggest that anxiety and depressive symptoms and disorders can occur earlier in life than previously thought, and appear to be on the increase. The burden that is associated with internalising symptoms is large, with children’s social, emotional and cognitive development negatively impacted. Research suggests that early intervention and prevention is vital for adaptive development, and this review set out to explore the literature regarding social-emotional learning programs for children of pre-school age that aim to prevent and reduce symptoms of anxiety and depression. The review focussed on interventions that could be delivered universally in the school context to children aged four to six years, or their parents. Only six programs were identified that met these criteria. The results of this review suggest that intervention and prevention efforts in early childhood are needed and can be effective in terms of reducing the burden associated with internalising symptoms in childhood, at least in the short term. This appears to be the case particularly when parents are actively involved in the intervention, too. However, more rigorous research is needed that involves larger randomised controlled trials with multiple reporters and consistent administration of assessments across the samples.